Wie normal ist die Norm? Sprachliche Normen im Spannungsfeld von Sprachwissenschaft, Sprachöffentlichkeit und Sprachdidaktik. - Hennig, Mathilde (Kassel University Press, 2009)
"How normal is the norm?" is the title of a research project on the relation of "sprachpflegerischer Normpostulat" and "Normbewusstheit" of the German language. The present volume assembles the findings of the linguistic research undertaken in the project.